2018
DOI: 10.1016/j.jid.2017.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Melanin Transferred to Keratinocytes Resides in Nondegradative Endocytic Compartments

Abstract: Melanin transfer from melanocytes to keratinocytes and subsequent accumulation in the supranuclear region is a critical process in skin pigmentation and protection against UVR. We have previously proposed that the main mode of transfer between melanocytes and keratinocytes is through exo/endocytosis of the melanosome core, termed melanocore. In this study, we developed an in vitro uptake assay using melanocores secreted by melanocytes. We show that the uptake of melanocores, but not melanosomes, by keratinocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 29 publications
(34 reference statements)
13
68
1
Order By: Relevance
“…A group of recent studies indicated that melanocores incorporated in keratinocytes are stored in organelles expressing lysosomal membrane proteins but lacking a membrane structure (Correia et al, ; Hurbain et al, ). Therefore, we examined PHEKs containing isolated melanosomes and also PHEKs containing isolated melanocores to determine whether PTPD‐12 could decrease the melanin content in those cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of recent studies indicated that melanocores incorporated in keratinocytes are stored in organelles expressing lysosomal membrane proteins but lacking a membrane structure (Correia et al, ; Hurbain et al, ). Therefore, we examined PHEKs containing isolated melanosomes and also PHEKs containing isolated melanocores to determine whether PTPD‐12 could decrease the melanin content in those cells.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, previous studies only showed steady‐state melanosomes that were readily transferred to keratinocytes, which might not reflect the range of dynamic intercellular communications that occur during melanosome uptake. The main mode of melanin transfer from melanocytes to keratinocytes is exo/endocytosis of the melanosome core, termed melanocore, which leads to the storage of melanin in endocytic compartments that are not highly acidic nor degradative (Correia et al, ). Therefore, we evaluated the effect of PTPD‐12 on melanin content in isolated melanosome‐laden keratinocytes as well as in melanocore‐containing keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…4i,j), our results have not yet revealed the fate of oxidized parkin in other neurons. Human LAMP proteins have been shown to store melanin in human keratinocytes to protect them from UV light 22 . Thus, oxidized parkin together with LAMP-3 (and possibly, LAMP-2) could play a similar role in the ongoing storage of neuromelanin and other radicals, thus facilitating their effective sequestration in ageing brain.…”
Section: Discussionmentioning
confidence: 99%
“…4i). Of note, LAMP homologues have been shown to promote long term storage of melanin in human keratinocytes 22 ; moreover, variants at the LAMP-3 locus have recently been linked to PD susceptibility 23 .…”
Section: Parkin Localizes To Lamp-3 + -Lysosomes Within Nigral Neuronsmentioning
confidence: 99%
“…To show if the melanin moves itself without membrane, electron tomography was used to obtain a better resolution. Recently, Correia et al (, in press) reported that the uptake of melanocores, but not melanosomes, by keratinocytes is protease‐activated receptor (PAR)‐2‐dependent. In addition, the endocytic regulators Rab5b, Rab7a, and Rab9a were reported as significant factors for melanocore uptake by keratinocytes (Correia et al, , in press).…”
Section: Discussionmentioning
confidence: 99%